Psikolojik ve sosyal yönleriyle kurban - Turan, Yahya (My University, 1999)
THE SACRIFICE THROUGH ITS PSYCHOLOGICAL AND SOCIALSIDES The aim of this thesis called the sacrifice through its psychological and social sides is to determine the social and economic factors that influence on today's human's behaviours of killing animals as a sacrifice and their attitudes to these animals. The work studied on the field of religion psychology consistsof five parts. 1. In the first part as introduction, it is given detail information about the applications of the sacrifice in different culturs and its historical development. 2. In the second part there is information that forms the theoretical frames of the subject. Also the definitions that determine the limits of the subject are considered in this part. 3. In the third part it is given information about the methods of the research. In that part, after givin information about the preparing and application of the pool, that is a form of getting information, the characteristics of the subjects are explained. 4. In the forth part the discoveries about the research are declared as tables. 5. And in the last part, some discussions and comments about these discoveries are mentioned. In the end, it is understood that the sacrifice is a worship and has been carried out from the primitive man up to now. When it is considered of the factors that influence on this worship through its deep history, it is mentioned that there is a significant relation among these below: Age, occupation, district, whether the house rented or not, salary, comprehension of religiousness, ideas about the Pilgrimage (Hajj), performing the Prayer (Salat), fasting, Welfaring money for the poor and behaviours of killing animals. Also one of the aims of this research is, comparing the groups, to determine the attitudes of the different groups to the sacrificial animals. After studying, in details, of demographic properties through the attitudes to the sacrificial animals, in other words, the state of the independent changeables in that research can be realized like that: Acording to the discoveries of the research, while independent changeables like age, occupation, education, sexuality, and in come do not influence of people's attitudes to the sacrificial animals, on the other hand, independent changeables like district and comprehension of religiousness, ideas about the Pilgrimage (Hajj) -one of the basic worships- and performing the Prayer (Salat) influence on attitudes to the sacrificial animals. Whether is there any relation or not bitween the death anxiety and the attitudes to the sacrificial animals is studied in details and the analysis demonstrates that there is no relation between the deat anxiety and the attitudes to the sacrificial animals. PSİKOLOJİK VE SOSYAL YÖNLERİYLE KURBAN Psikolojik ve Sosyal Yönleriyle Kurban adlı bu tezin amacı, günümüz insanlarının kurban kesme davranışları ve kurbana karşı tutumlarına etki eden sosyo-ekonomik faktörleri tespit etmektir. Din psikolojisi alanında yapılan bu çalışma beş bölümden oluşmaktadır. I. Bölüm olan girişte kurbanın değişik kültürlerde uygulanışı ve tarihi gelişimi verilmiştir. II. Bölümde konunun teorik çerçevesini oluşturan bilgiler yer almaktadır. Konunun sınırlarını belirleyen tanımlar da bu bölümde ele alınmıştır. III. Bölümde araştırmanın metodolojisi hakkında bilgi verilmiştir. Bu bölümde bilgi toplama formu olan anketin hazırlanış ve uygulanışı hakkında bilgi verildikten sonra deneklerin nitelikleri açıklanmıştır. IV. Bölümde araştırma ile ilgili elde edilen bulgular tablolar halinde verilmiştir. V. Ve sonuç bölümünde ise elde edilen bulgular çerçevesinde yapılan tartışma ve yorumlara yer verilmiştir. Sonuç olarak kurbanın, ilk insandan günümüze kadar bütün toplumlarda uygulana gelen bir ibadet olduğu görülmüştür. Derin geçmişe sahip olan bu ibadete etkisi olan faktörlere bakıldığında yaş, meslek, oturulan semt, oturulan evin kira olup olmaması, aylık gelir, dindarlık algısı, hac konusundaki kanaatler, namaz kılma durumu (sıklığı) oruç tutma, zekat verme durumları ile kurban kesme davranışı arasında manidar bir ilişkinin olduğu ortaya çıkmıştır. Bu araştırmanın amaçlarından biri de gruplar arası karşılaştırmalar yaparak farklı grupların kurbana karşı tutumlarını tespit etmektir. Kurbana karşı tutumları bakımından incelenen demografik özelliklerin yani bu araştırmadaki bağımsız değişkenlerin durumu şöyle değerlendirilebilir: Araştırma bulgularına göre yaş, meslek, eğitim, cinsiyet, gelir gibi bağımız değişkenler halkın kurbana karşı tutumlarını etkilemezken, oturulan semt ve dindarlık algısı, temel ibadetlerden hac konusundaki kanaatler ve namaz kılma durumu gibi bağımsız değişkenler kurbana karşı tutumları etkilemektedir. Bir alt problem olarak ölüm kaygısı ile kurbana karşı tutumlar arasında bir bağıntı olup-olmadığı incelenmiş, yapılan analiz (korelasyon), ölüm kaygısı ile kurbana karşı tutumlar arasında bir bağıntının olmadığını ortaya çıkarmıştır.
Keywords: KURBAN